Running Up That Hill: Fitness in the Face of Recession - Kerry L. Papps; Alex Bryson; J. James Reade (Institute of Labor Economics (IZA), 2023)
Drawing on 28 million observations on people's running times in a free weekly 5 kilometre running event, Parkrun, we examine whether labour market conditions affect fitness. Running times improve during recessions for men and women aged 50 and above but worsen for men aged 20-49 and women aged 20-29, suggesting that the fall in the opportunity costs of fitness during recessions is the dominant factor for elderly runners, whereas the income effect induced by unemployment dominates for prime age workers. Participation in Parkrun is not sensitive to the business cycle so our results are not driven by compositional changes.
Keywords: I12; I30; 330; business cycle; health; fitness; Parkrun